Social Coordination and Public Policy: Explorations in Theory and Practice - Herzberg, Roberta; Roberts, Gavin; Wolf, Brianne (Lexington Books, 2023)
This volume explores, both in theory and in practice, what “social coordination” is and how public policies can help or hinder the processes of social coordination. In particular, these chapters examine the institutional incentives that motivate public policy decisions and their implementation to achieve specific individual and social goals. Some chapters in this volume are more theoretical, applying insights from the Austrian, Virginia, and Bloomington schools of political economy to public policy issues. Other chapters are more practical, exploring the broader implications of these theories to real-world public policy puzzles. Authored by individuals from a variety of disciplines with diverse interests in public policy, this work includes discussions of topics such as environmental policy, housing policy, and education policy, among others. A unifying theme across the chapters is that policymakers often advise one-size-fits-all solutions to complicated public policy questions but ignore the multitude of incentives faced by the “players of the game” and the subsequent development of diverse forms of social coordination. Social coordination is often left out public policy analysis but is crucial to the success of informal and formal institutional arrangements. The chapters aim to disentangle these issues of social coordination in public policy in theory and practice.